Request of pharmaceutical care service in a private owned community pharmacy. - Pires CF; Costa MM; Angonesi D; Borges FP (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Pharmacists, more than drug producer, is being a co-responsible for drug therapy and promoter of the rational use of medicines, enhancing their role. Appearance of a new philosophy, pharmaceutical care, came to organize, enhance and allowing this new role of the pharmacist in primary health care. Objectives of the present study were to determine the existence and to characterize the request for pharmaceutical care services and to assess the wiliness to pay for these services in a privately owned community pharmacy. An interview following a check-list was used by researchers to gather data. In 236 interviewed customers, 88.1% did not know the term 'pharmaceutical care', 67.2% showed to be interested on the service. Regarding the wiliness to pay, 39.9% conditioned it to the amount, and 10.1% stated that they would pay for the service. This allows us to conclude than in this setting, a demand existed, what allows repeating this survey in other settings, what lead us to the necessity of defining a standard of practice in Brazil, and in the rest of the world, to provide care to those who need it.